All around the farm - Low, Alice; Swanson, Maggie (New York : Random House, 1984)
Fold-out board pages with flaps to lift reveal the delights of visiting a farm.
Cover title.
Keywords: Children's stories, American; Toy and movable books -- Specimens; Farm life -- Fiction; Stories in rhyme; Toy and movable books